Quality of Work Life: The Context of the Influence of Servant Leadership and Psychological Empowerment with Trust Mediation at PT. Yamatogomu Indonesia in Purwakarta - Patminingsih Patminingsih; Retno Purwani Setyaningrum (Journal of Research in Social Science and Humanities, 2025)
This study aims to examine the influence of servant leadership and psychological empowerment on the quality of work life with trust as a mediating variable. The research was conducted on employees of PT Yamatogomu Indonesia (YGI). At PT YGI, there are 190 employees, so the sample used consisted of 128 employees, where the sample was taken using the Slovin formula with a margin of error tolerance of 5% or 0.05. The data obtained were then analyzed using partial least square (PLS) with the structural equation model (SEM) technique through the SmartPLS 4.1.1 software to evaluate the validity, reliability, and relationships between variables. The analysis results show that servant leadership significantly affects trust, trust significantly affects quality of work life, servant leadership significantly affects quality of work life, servant leadership significantly affects trust through quality of work life, psychological empowerment significantly affects trust, psychological empowerment significantly affects quality of work life, and psychological empowerment significantly affects trust through quality of work life.